Hybrid Tri-Co-60 MRI radiotherapy for locally advanced rectal cancer: An in silico evaluation. (June 2018) - Boldrini, Luca; Placidi, Elisa; Dinapoli, Nicola; Azario, Luigi; Cellini, Francesco; Massaccesi, Mariangela; Chiesa, Silvia; Gambacorta, Maria Antonietta; Mattiucci, Gian Carlo; Piccari, Danila; Teodoli, Stefania; De Spirito, Marco; et al.
Highlights: Tri-Co-60 MRI radiotherapy (RT) is feasible in locally advanced rectal cancer. Larger volumes of normal tissue receive low-moderate doses in Tri-Co-60 MRI RT. Further studies on functional imaging applications and LinacMRI approach are needed. Tri-Co-60 MRI might represent a safe irradiation technique for pelvic tumors. Abstract: Introduction: Aim of this paper is to investigate the plan quality of a tri-Co-60 MRI-Hybrid system for intensity-modulated radiation therapy (IMRT) in patients affected by locally advanced rectal cancer (LARC) undergoing neo-adjuvant radiotherapy. Materials and methods: Ten consecutive LARC patients were selected. Tri-Co-60 step and shoot IMRT plans were generated simulating the presence of the magnetic field (Bon ) or not (Boff ) with the dedicated treatment planning system (TPS). The total planned dose was 45 Gy in 25 fractions to the mesorectum and the pelvic nodes (planning target volume 2, PTV2) and 55 Gy to the tumor and correspondent mesorectum (PTV1) through simultaneous integrated boost (SIB). Tri-Co-60 IMRT plans were compared with Volumetric Modulated Arc Therapy (VMAT) and IMRT plans for Linear Accelerator (Linac). Results: Bon and Boff tri-Co-60 IMRT plans showed no relevant differences. Mean values of PTV1 and PTV2 receiving at least 95% of the Dp (V95% ) were higher than 95% in all treatment plans. All plans met the V105% constraint for the PTV1. Mean values of V105% for the PTV2 were 14.8, 5.0, and 7.3% respectively for tri-Co-60, VMAT and IMRT. Mean Wu's HI values were similar in all plans (7.4–7.8%). All plans met the V45Gy constraint for small bowel, but mean V45Gy value was higher with tri-Co-60. Bladder irradiation was comparable and always lower than the chosen D max 65 Gy constraint. Mean values of V5Gy and V20Gy to the body and median skin doses were higher with tri-Co-60 plans. Discussion: Treatment plans with Tri-Co-60 step and shoot IMRT met the dose-volume objectives in patients with LARC. Nevertheless, a larger volume of normal tissue received low-moderate doses when compared with Linac based VMAT and IMRT.